Related health burden with the improvement of air quality across China - Huaiyue Xu; Qing Wang; Huanhuan Zhu; Yayi Zhang; Runmei Ma; Jie Ban; Yiting Liu; Chen Chen; Tiantian Li; Jing Ni; Xuehong Zhang (Chinese Medical Journal)
Abstract. Background:. Substantial progress in air pollution control has brought considerable health benefits in China, but little is known about the spatio-temporal trends of economic burden from air pollution. This study aimed to explore their spatio-temporal features of disease burden from air pollution in China to provide policy recommendations for efficiently reducing the air pollution and related disease burden in an era of a growing economy. Methods:. Using the Global Burden of Disease method and willingness to pay method, we estimated fine particulate matter (PM2.5) and/or ozone (O3) related premature mortality and its economic burden across China, and explored their spatio-temporal trends between 2005 and 2017. Results:. In 2017, we estimated that the premature mortality and economic burden related to the two pollutants were RMB 0.94 million (68.49 per 100,000) and 1170.31 billion yuan (1.41% of the national gross domestic product [GDP]), respectively. From 2005 to 2017, the total premature mortality was decreasing with the air quality improvement, but the economic burden was increasing along with the economic growth. And the economic growth has contributed more to the growth of economic costs than the economic burden decrease brought by the air quality improvement. The premature mortality and economic burden from O3 in the total loss from the two pollutants was substantially lower than that of PM2.5, but it was rapidly growing. The O3-contribution was highest in the Yangtze River Delta region, the Fen-Wei Plain region, and some western regions. The proportion of economic burden from PM2.5 and O3 to GDP significantly declined from 2005 to 2017 and showed a decreasing trend pattern from northeast to southwest. Conclusion:. The disease burden from O3 is lower than that of PM2.5, the O3-contribution has a significantly increasing trend with the growth of economy and O3 concentration.